O zanikaniu drgań swobodnych w pewnym układzie mechanicznym z nieliniową wibroizolacją - ŁAŃCZAK, Władysław (Engineering Transactions, 1970)
On the disappearance of free vibrations in a certain mechanical system with nonlinear vibro-insulationIn this paper are considered the free vibrations or a system with a nonlinear characteristics or elasticity and damping. The nonlinear characteristic of damping is caused by dry friction. For the solution of the nonlinear differential equation, the asymptotic method is used as given by Krylov and Bogolyubov.In the analysis or the free vibration, relationships are given by means oC which the envelopes of the amplitudes of vibration can be determined, the time of duration of the vibrating motion, and the number of vibrations after which the further motion is non-alternative.Numerical calculations are mad e for various combinations of the dimensionless parameters of the system, the results of which are presented graphically. Subsequently are given the conclusions of the analysis of vibration or the system discussed.In conclusion, the oscillograms of the investigations conducted are presented.